Information literacy and information skills instruction : new directions for school libraries - Thomas, Nancy Pickering; Crow, Sherry R.; Henning, Judy A.; Donham, Jean (Santa Barbara, California: Libraries Unlimited, 2020)
"This updated edition includes new and relevant research on information literacy, pedagogy, and skills instruction"--
Includes bibliographical references (pages 223-259) and index.
Keywords: Library orientation for school children -- United States; Library orientation for high school students -- United States; School libraries -- Activity programs -- United States; Information literacy -- Study and teaching (Elementary) -- United States; Information literacy -- Study and teaching (Secondary) -- United States